2004
DOI: 10.1016/j.amjhyper.2003.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Glucose effectiveness is strongly related to left ventricular mass in subjects with stage I hypertension or high-normal blood pressure

Abstract: In this sample of nonobese and glucose-tolerant subjects with an early stage of hypertension, SG but not SI was related to LVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Overall, the association was independent of age, degree of obesity, renal function, HTN and other potential confounding factors, including DM and HL. [23][24][25][26] This finding is consistent with the results of an experimental study that have reported allopurinol-treated rats developing significantly less cardiac hypertrophy with negligible effects on BP, 4 and is also in agreement with the current understanding of the association as observed in small samples of hypertensive patients. 5,6 We have demonstrated the association in more detail in a large sample of apparently healthy individuals not taking medication for HTN, and have also revealed a significant independent association in normotensive as well as hypertensive subjects.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Overall, the association was independent of age, degree of obesity, renal function, HTN and other potential confounding factors, including DM and HL. [23][24][25][26] This finding is consistent with the results of an experimental study that have reported allopurinol-treated rats developing significantly less cardiac hypertrophy with negligible effects on BP, 4 and is also in agreement with the current understanding of the association as observed in small samples of hypertensive patients. 5,6 We have demonstrated the association in more detail in a large sample of apparently healthy individuals not taking medication for HTN, and have also revealed a significant independent association in normotensive as well as hypertensive subjects.…”
Section: Discussionsupporting
confidence: 81%
“…The odds ratios (OR) and their 95%CI of LVH according to UA level were calculated by multivariate logistic regression analysis adjusting for known confounding factors such as age, BMI, 21 Creat 22 and HTN in addition to the institute (model 1), and by potential confounding factors such as HL 23,24 and DM (model 2). 25,26 We conducted the model-2 analysis using samples stratified by BP. We added SBP as an adjustment factor in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, decreased glucose effectiveness (but not insulin sensitivity) has been found in patients with other features of the metabolic syndrome, such as increased blood pressure and an enlarged left ventricular mass (38). Furthermore, a causeeffect relationship between elevated free fatty acids and decreased glucose effectiveness has been recently suggested in diabetic individuals (29).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin and leptin both stimulate cardiac growth in isolated cardiomyocytes, suggesting that diet-induced increases in their circulating concentrations could stimulate LVH independent of afterload 3, 11, 12 . In patients with hypertension there is a positive relationship between plasma insulin concentration and LVH that is independent of blood pressure [13][14][15][16] . In addition, increased plasma leptin levels are correlated with LVH and congestive heart failure 17, 18 .…”
Section: Introductionmentioning
confidence: 99%